Response and Potential Indication to Hypoxia in the Changjiang River Estuary and its Adjacent Waters: Insight From Redox-Sensitive Trace Elements in Sediment Core - Zhang, Xiaotong; Yuan, Huamao; Song, Jinming; Duan, Liqin (Frontiers in Earth Science, 2022)
The migration and enrichment of redox sensitive trace elements (RSEs) from seawater to sediments are controlled not only by their geochemical properties but also by marine redox conditions. Therefore, RSEs, such as Mo, U, and V, are extensively used to indicate redox states in marine environments. To retrieve the historical redox state in hypoxic zone near the Changjiang River Estuary Adjacent Waters, the distribution and enrichment degree of Mo, U, and V in a sediment core collected from the recurrently hypoxic region were investigated. The correlation analysis shows that the authigenic enrichment of Mo and U in sediment core 3050-2 are primarily controlled by redox conditions, rather than sediment grain size, adsorption on organic matters, Fe-Mn (hydr)oxides, and terrigenous detritus input. Mo-U covariation is selected to analyze the evolution of redox conditions in the seasonally hypoxic zone. The MoEF/UEF values in this sediment core are almost between 0.1 and 0.3×Mo/Umodern seawater value and show a general decreasing trend with depth, indicating an overall progressive transition from oxic to suboxic conditions in this area since 2005. The close MoEF/UEF values and similar chronological Mo-U variations by comparing our results with previous study in adjacent area offer common evidence for the gradually intensified bottom water oxygen stress, suggesting the possible application of MoEF/UEF in retrieving redox development in this coastal hypoxic zone.